2023
DOI: 10.3390/nu15030764
|View full text |Cite
|
Sign up to set email alerts
|

Association between Food, Beverages and Overweight/Obesity in Children and Adolescents—A Systematic Review and Meta-Analysis of Observational Studies

Abstract: A healthy diet is essential to prevent childhood obesity, however, adherence to a healthy diet is challenging. The aim of this study was to give a comprehensive overview of the literature investigaating associations between food and beverages and overweight/obesity in children and adolescents in order to identify dietary risk factors. A systematic search was performed in four databases and observational studies were included. Meta-analysis was performed using the random effect model. Sixty records met inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…In terms of epidemiological studies, both food quality and quantity may affect health outcomes [120][121][122][123][124][125]. For example, a higher intake of comfort foods may be associated with rates of obesity or overweight [126,127]. However, a moderate intake of such foods has less of an effect on health outcomes [128][129][130][131].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of epidemiological studies, both food quality and quantity may affect health outcomes [120][121][122][123][124][125]. For example, a higher intake of comfort foods may be associated with rates of obesity or overweight [126,127]. However, a moderate intake of such foods has less of an effect on health outcomes [128][129][130][131].…”
Section: Discussionmentioning
confidence: 99%
“…Abbasalizad Farhangi et al 42 show in 33 studies with 121,282 individuals, that excessive intake of sugary drinks was associated with an increase of 0.75 kg/m 2 in BMI and abdominal circumference in children and adolescents. Jakobsen et al 43 . concluded that greater intake of sugary drinks increased the chances of overweight/obesity by 1.20.…”
Section: School Periodmentioning
confidence: 99%
“…Globally, childhood overweight and obesity are expected to increase by 60% and reach an estimated 250 million children in 2030 (World Health Organization [WHO], 2020). Childhood obesity accounts for 30% of all obesity cases, and therefore, it is important to acquire adequate and balanced nutrition and regular physical activity habits in early childhood and adolescence, which will play a decisive role in the health profile in adulthood (Jakobsen et al., 2023).…”
Section: Introductionmentioning
confidence: 99%